Her last whisper : a novel - Robards, Karen (Robards, Karen. Charlotte Stone novel., 2014)
"After a brush with death while chasing down a brutal murderer with the FBI, serial killer expert Dr. Charlotte Stone wants nothing more than to retire to her research on criminal psychology. But when a colleague, Special Agent Lena Kaminsky, suspects her missing sister has fallen prey to the vicious Cinderella Killer, Charlie rushes to her side. Along with Special Agents Tony Bartoli and Buzz Crane--and of course, Michael Garland, the ever-present, fatally sexy ghost who goes where she does--Charlie heads to Las Vegas to track down the predator before it's too late. The team doesn't realize that this killer targets single, beautiful women and courts them before brutally ending their lives. Now he's got his sights set on Charlie--and is closer than anyone suspects"--